2011
DOI: 10.1103/physrevb.84.075417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N doping on the electronic properties of a small carbon atomic chain with distinctsp2terminations: A first-principles study

Abstract: Carbon nanostructures consisting of corannulene/coronene-like pieces connected by atomic chains and doped with nitrogen atoms have been addressed by carrying out first-principles calculations within the framework of the spin-polarized density functional theory. Our results show that the conformation, charge distributions, and spin states are significantly influenced by the nitrogen incorporation in comparison to these characteristics of similar pure carbon structures. Higher concentration of incorporated nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 36 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…In all the available experimental reports, the dopant atoms are randomly distributed in the graphene sheets [14,15]. However, theoretical investigations have suggested that periodically arranged dopants may bring about interesting new properties [16][17][18]. For example, Casolo et al have reported that when the substitutional defects are arranged in D 6h symmetry, the Dirac cones can be preserved; otherwise, a band gap is open [19].…”
Section: Introductionmentioning
confidence: 99%
“…In all the available experimental reports, the dopant atoms are randomly distributed in the graphene sheets [14,15]. However, theoretical investigations have suggested that periodically arranged dopants may bring about interesting new properties [16][17][18]. For example, Casolo et al have reported that when the substitutional defects are arranged in D 6h symmetry, the Dirac cones can be preserved; otherwise, a band gap is open [19].…”
Section: Introductionmentioning
confidence: 99%
“…In our first-principles calculations, we adopt the Vienna Ab Initio Simulation Package (VASP) equipped with the projector-augmented-wave (PAW) method to study the electron-ion interactions [34]. The Perdew-Burke-Ernzerh (PBE) functional of the generalized gradient approximation (GGA) is considered to treat the electron exchange correlation, which produces the correct ground-state structure of the combined systems [35,36,37]. In our calculations, the model of the 2 × 2 × 1 pristine single-layer PdSe 2 (24 atoms) is given, the distance between adjacent PdSe 2 layer set as 20 Å to avoid the effects induced by periodic boundary conditions.…”
Section: Theoretical Model and Computational Detailsmentioning
confidence: 99%
“…[12][13][14][15] At the atomic level, a one-dimensional (1D) nanowire device represents the ultimate limit in nanoelectronics. 6,16 Hence, by considering distinct stable atomic chains, [18][19][20][21][22][23][24] one may attain small and robust circuit elements integrated with other electronic components. 25,26 In this direction, 1D carbon chains may play a central role in miniaturization of electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on density functional theory (DFT) computational simulations 37,38 and the proposed molecular devices are obtained as structurally stable systems. Based on the electronic behavior of other carbon-atomic-wire systems, 22,23 we have selected chains containing an even/odd number of carbon atoms.…”
Section: Introductionmentioning
confidence: 99%